Monitoring haemodynamic adaptation in athletes involved in cyclic sports - Zaharova, A.V.; Rapoport, L.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to substantiate the results of monitoring long-term haemodynamic adaptation in athletes involved in cyclic sports for the purpose of planning and/or correcting the training process. Methods and structure of the study. To substantiate the patterns of long-term haemodynamic adaptation of athletes to natural growth and development in combination with increasing physical loads during long-term training, haemodynamic monitoring was performed in an orthostatic test (AOT) in successful female cross-country skiers (n=310), biathletes (n=23), male cross-country skiers (n=533), biathletes (n=33) aged 9-18 who took leading places in cross-country skiing competitions at the regional level in the Russian Federation (1st-6th place), and highly qualified athletes aged 19-35 who participated in the Russian Championships. The sample of successful athletes included 4 Honoured Masters of Sport of Russia, 8 International Class Masters of Sport and 213 Masters of Sport. Results and conclusions. The study of age-related patterns of long-term haemodynamic adaptation in successful male and female cross-country skiers and the subsequent statistical processing of the data obtained made it possible to determine the model indicators for athletes in cyclic sports based on the most informative haemodynamic parameters. The developed algorithm for interpreting the results of pedagogical control of long-term haemodynamic adaptation of athletes provides for the rational management of training loads with the aim of forming the necessary and sufficient level of haemodynamic adaptation.